Lesões: psicologia do esporte e os períodos pré e pós lesão - Faria, Lucas Corrêa [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
An athlete's career development can be associated with a number of factors that are essential for optimal performance. In addition to physical and technical factors, psychological factors must be addressed, which can be linked to the emotional and motivational balance (adherence) of athletes to sports injuries that they are prone to have due to the aspects already mentioned. From this, sports psychology can be an important tool in the pre and post injury period, either as prevention or intervention of a case, individually or in the group that is inserted, thus avoiding possible scenarios of withdrawal or new injuries. Thus, this study aims to analyze and understand the causes of sports injuries and their entire process, which can directly or indirectly affect athletes, coaches, family members and fans. In order to achieve the objective described above, the bibliographic research was chosen to deepen and comprehend the theme, enabling new perspectives, visions and tracing contextualized bridges on the subject. Thus, it was possible to deepen the theoretical approach on the subject studied here, verifying that sports injuries can generate several implications in the athletes' lives, whether related to personal or professional aspects. Thus, the work and monitoring of the sports psychologist at various stages of the process is essential, helping to improve rehabilitation and return to the practice of sports.

O desenvolvimento da carreira de um atleta pode estar associado a diversos fatores imprescindíveis para uma performance ideal. Além dos fatores físicos e técnicos, deve-se trabalhar fatores psicológicos, que podem ser interligados ao equilíbrio emocional e motivacional (de adesão) dos atletas perante as lesões esportivas que esses estão sujeitos a ter devido aos aspectos já citados. A partir disso, a psicologia esportiva pode ser uma importante ferramenta no período pré e pós lesão, seja com a prevenção ou intervenção de um caso, individual ou no grupo que está inserida, assim evitando possíveis cenários de desistência ou novas lesões. Com isso, o presente estudo possui como objetivo analisar e interpretar as causas das lesões esportivas e todo seu processo, que pode afetar diretamente ou indiretamente, atletas, técnicos, familiares e torcida. Para a consecução do objetivo descrito anteriormente, optou-se pela pesquisa bibliográfica para maior aprofundamento e compreensão do tema, possibilitando novos olhares, visões e traçando pontes contextualizadas sobre o assunto. Assim, foi possível maior aprofundamento teórico acerca do tema aqui estudado, verificando que as lesões esportivas podem gerar diversas implicações na vida dos atletas, sejam referentes a aspectos pessoais ou profissionais. Assim, é essencial o trabalho e acompanhamento do psicólogo do esporte em diversas fases do processo, auxiliando em melhora na reabilitação e volta à prática da modalidade esportiva.
Injuries: sports psychology and the pre & post injury periods
Keywords: Sports injuries; Rehabilitation; Emotional states; Psychological aspects; Lesões esportivas; Reabilitação; Estados emocionais; Aspectos psicológicos